Crystallization and preliminary x-ray characterization of a lectin from Cicer arietinum (chickpea) - Katre, Uma V.; Gaikwad, S. M.; Bhagyawant, S. S.; Deshpande, U. D.; Khan, Mohammad Islam; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Structural and active site modification studies implicate Glu, Trp and Arg in the activity of xylanase from alkalophilic Bacillus sp (NCL 87-6-10) - Balakrishnan, H.; Satyanarayana, L.; Gaikwad, S. M.; Suresh, C. G. (Enzyme and Microbial Technology, 2006)
Structural studies and residue modification using group specific reagents were used to ascertain the role of different functional groups in xylanase from alkalophilic Bacillus sp. (NCL 87-6-10). Treatment with N-bromosuccinimide resulted in fast enzyme inactivation. Reaction with Woodward's reagent K resulted in initial fast followed by slower inactivation. In both cases enzyme was protected against inactivation by the substrate, xylan. The reaction of the enzyme with phenylglyoxal has revealed one essential arginine residue at the active site. The three-dimensional structural analysis of the xylanase at 2.8 angstrom resolution also implicates involvement of Trp, and Arg residues and carboxylate groups in the binding of substrate and in the catalysis of xylanase. (c) 2005 Published by Elsevier Inc.
Keywords: active-site residues; alkaline xylanase; Chemical modification; three-dimensional structure

Interaction of alpha-mannosidase from aspergillus fischeri with glycosidase inhibitors, metal ions and group specific reagents - Shashidhara, K. S.; Gaikwad, S. M.; Khan, Mohammad Islam; Bharadwaj, Kishor Chandra; Pandey, G. (Research Journal of Biotechnology, 2009)
As an initial step towards using alpha-mannosidase as a target against anticancer drugs, inhibition studies of a model enzyme, class II alpha-mannosidase from Aspergillus fischeri in presence of polyhydroxy piperidine derived glycosidase inhibitors, metal ions and amino acid specific reagents were carried out to reveal the sensitivity of the enzyme. Three of the derivatives (Compound 20, 32 and 39)(11) showed competitive inhibition (K(i) =45, 48 and 235 mu M) and the binding of the inhibitors to the enzyme was entropically driven. Among the metal ions checked, Cu(++) (K(i) = 21nm) and Se(++) ions (K(i) = 32 mu M) showed noncompetitive and Co(++) (K(i) = 1.195 mM) showed competitive inhibition of the enzyme activity with insignificant change in the secondary structure of the protein. The above studies exhibit the Potential of the enzyme in studying anticancer drugs. Treatment of the enzyme with group specific reagents showed the presence of carboxylate, Arg and Cys at the active site. Substrate protection studies and kinetics of the modified enzyme confirmed the above results. Trp and His at the active site were observed to be in proximity.
Keywords: active-site; alpha-Mannosidase; Chemical modification; Glycosidase inhibitors; metal ions

Differential accumulation of gliadin proteins in wheat grain of RILs grown at two different agroclimatic conditions and their effect on loaf volume - Elangovan, M.; Dholakia, Bhushan B.; Gaikwad, S. M.; Gupta, V. S. (Australian Journal of Crop Science, 2010)
The end use of wheat depends on the quality and quantity of protein accumulated in the grain during the grain filling stage. Gliadin families of proteins are proved to affect the bread making quality (BMQ) by affecting the rheology and functionality of dough. The gliadin accumulation was analysed using Indian genotypes grown in two diverse agro climatic zones. About 16 RILs along with their parents HI977 and HD2329 revealed significant difference in accumulation of all gliadin fractions. High accumulation of alpha and beta gliadin with low level of gamma gliadin was observed for Kota as compared to Pune location. However, this significant difference in gliadin accumulation due to environment, did not affect the loaf volume performance of the RILs at statistically significant level.
Keywords: loaf volume (Lv); RP-HPLC; Wheat protein